1995
DOI: 10.1104/pp.109.4.1363
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Development of Peroxisomes and Glycolate Metabolism among Algae of Different Evolutionary Lines of the Prasinophyceae

Abstract: Leaf-type peroxisomes are not present i n the primitive unicellular Prasinophycean line of algae but are present in the multicellular algae Mougeotia, Chara, and Nitella, which are i n the one evolutionary line, Charophyceae, that led t o higher plants. Processes related to glycolate metabolism that may have been modified or induced with the appearance of peroxisomes have been examined. The algal dissolved inorganic carbon-concentrating mechanism and alkalization of the medium during photosynthesis were not lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In C. reinhardtii, catalase is found in the mitochondria (Kato et al 1997). On the other hand, in the multicellular green algae Mougeotia, Chara and Nitella (Charophyceae), which are found along the evolutionary line of higher plants, the microbodies contain enzymes attributed to the leaf peroxisomes of higher plants (Kehlenbeck et al 1995). In our previous paper, we reported that GFP proteins fused with the PTS sequences transported into the microbodies of C. ehrenbergii of Charophyceae (Shinozaki et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…In C. reinhardtii, catalase is found in the mitochondria (Kato et al 1997). On the other hand, in the multicellular green algae Mougeotia, Chara and Nitella (Charophyceae), which are found along the evolutionary line of higher plants, the microbodies contain enzymes attributed to the leaf peroxisomes of higher plants (Kehlenbeck et al 1995). In our previous paper, we reported that GFP proteins fused with the PTS sequences transported into the microbodies of C. ehrenbergii of Charophyceae (Shinozaki et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…; Kehlenbeck et al . ; Igamberdiev & Lea ). Recently, it was shown that photorespiratory glycolate oxidases in plants ( e.g.…”
Section: Impact Of Peroxisome Specialisation On Photorespirationmentioning
confidence: 99%
“…Kehlenbeck et al . ; Igamberdiev & Lea ). Early biochemical studies demonstrated the operation of photorespiration in the diatoms Cylindrotheca fusiformis , Nitzschia alba and Thallassiosira pseudonana (Paul & Volcani , ; Paul et al .…”
Section: Alternative Photorespiratory Routesmentioning
confidence: 99%
“…The suspension was centrifuged at 30,000g for 6 min at 4°C (Kehlenbeck et al 1995). The supernatant was removed and the cell pellet was frozen overnight at -20°C.…”
Section: Measurement Of Glycolic Acid Contentmentioning
confidence: 99%